Accelerated long‐term forgetting in individuals with subjective cognitive decline and amyloid‐β positivity. (15th April 2021) - Tort‐Merino, Adrià; Valech, Natalia; Laine, Matti; Olives, Jaume; León, María; Ecay‐Torres, Mirian; Estanga, Ainara; Martínez‐Lage, Pablo; Fortea, Juan; Molinuevo, José Luis; Sánchez‐Valle, Raquel; Rodriguez‐Fornells, Antoni; et al.
Abstract: Objectives: We studied a sample of cognitively unimpaired individuals, with and without subjective cognitive decline (SCD), in order to investigate accelerated long‐term forgetting (ALF) and to explore the relationships between objective and subjective cognitive performance and cerebrospinal fluid (CSF) Alzheimer's disease (AD) biomarkers. Methods: Fifty‐two individuals were included and SCD was quantified through the Subjective Cognitive Decline Questionnaire (SCD‐Q), using its validated cutoff to classify participants as Low SCD‐Q ( n = 21) or High SCD‐Q ( n = 31). These groups were further subdivided according to the presence or absence of abnormal levels of CSF Aβ42 . Objective cognitive performance was assessed with the Ancient Farming Equipment Test (AFE‐T), a new highly‐demanding test that calls for acquisition and retention of novel object/name pairs and allows measuring ALF over a 6‐month period. Results: The High SCD‐Q group showed a significantly higher free forgetting rate at 3 months compared to the Low SCD‐Q ( F [1, 44] = 4.72; p < 0.05). When stratifying by amyloid status, High SCD‐Q/Aβ+ showed a significantly lower performance than High SCD‐Q/Aβ–on the final free and cued learning scores ( F [1, 27] = 6.44, p < 0.05 and F [1, 27] = 7.51, p < 0.05, respectively), the 1‐week free and cued recall ( F [1, 24] = 4.49; p < 0.05 and F [1, 24] = 7.10; p < 0.01, respectively), the 1‐week cued forgetting rate ( F [1, 24] = 5.13; p < 0.05), and the 3‐month cued recall ( F [1, 24] = 4.27; p < 0.05). Linear regression analyses showed that higher SCD‐Q scores were associated with higher forgetting rates on the AFE‐T ( β = −0.212; p < 0.05). Conclusions: It is possible to detect ALF in individuals with high SCD ratings, appearing especially in those with abnormal CSF Aβ42 levels. Both in research and the clinical field, there is an increasing need of using more demanding cognitive measures, such as the AFE‐T, for identifying and tracking the earliest cognitive changes in these populations. Key Points: We assessed accelerated long‐term forgetting (ALF) in subjective cognitive decline (SCD) We found ALF over 3 months in individuals with high SCD ratings Individuals with high SCD ratings and abnormal Aβ42 levels displayed higher forgetting rates ALF might be a potential marker of subtle cognitive dysfunction in the AD continuum